Innovative Design of an Augmented Reality Device for Anesthesia: User Insights and Usability Evaluation - Guise, Honoré; Marcilly, Romaric; Lecoutre, Arthur; Nunes, Frédérico; Jeanne, Mathieu; Ben Othman, Sarah; Hammadi, Slim; Lebuffe, Gilles; Odou, Pascal; Decaudin, Bertrand (Studies in health technology and informatics, 2025)
Patient care involves multiple healthcare professionals and carries inherent risks. Addressing human factors is essential to mitigating these risks and improving professional practices. Cognitive aids are one strategy to standardize tasks based on clinical guidelines. A multidisciplinary team, consisting of anesthesiologists, pharmacists, ergonomists, and engineers, aimed to design an innovative device to facilitate cognitive aid usage. The initial phase of the project involved evaluating the usability and utility of a prototype: augmented reality eyewear controlled by voice commands. Usability was assessed using the System Usability Scale (SUS), alongside semi-structured interviews conducted between July and August. A pharmacy resident conducted 13 interviews with anesthesiologists recruited from three hospitals within the Lille University Hospital Center, using a nine-question guide developed with an ergonomist. Interviews averaged 35.9 minutes (±10.4), and the average SUS score was 72.5 (±15.6). The prototype was generally well received, with participants suggesting the integration of cognitive aids for emergency situations. However, despite positive feedback on the concept, the format of the prototype was not favored. Ergonomic feedback will guide further device improvements, and additional research on technology adoption is required.